Effect of the Si/TiO2/BiVO4 Heterojunction on the Onset Potential of Photocurrents for Solar Water Oxidation - Jung, Hyejin; Chae, Sang Youn; Shin, Changhwan; Min, Byoung Koun; Joo, Oh-Shim; Hwang, Yun Jeong (American Chemical Society, 2015)
BiVO4 has been formed into heterojutictions with other metal. oxide semiconductors to increase the efficiency- for solar water oxidation. Here, we suggest that heterojunetion photoanodes of Si and BiVO4 can also increase the efficiency of charge separation and reduce the onset potential of the photocurrent by utilizing the high conduction band edge, potential of Si in a dual-absorber system. We found that a thin TiO2 interlayer is required in-this strucutre to realize 0 2 ma/ suggested photocurrent density enhancement and shifts in onset potential. Si/TiO2/BiVO4 photoandoes showed 1.0-MA/cm(2) at 1.23 V versus the reversible hydrogen electrode (RUE) With 0.11 y (vs RHE) of onset potential, which were a 3.3-fold photocurrent density enhancement and a negative shift in onset potential BiVO4 phutoanodes,
Keywords: BIVO4 PHOTOANODES; CHARGE SEPARATION; EFFICIENT; OXIDE; PHOTOELECTRODES